Characterization of 'Olivastro di Bucchianico cv' extra virgin olive oils and its recognition by HS‐GC‐IMS. (6th May 2021) - Di Serio, Maria Gabriella; Giansante, Lucia; Del Re, Paolo; Pollastri, Luciano; Panni, Filippo; Valli, Enrico; Di Giacinto, Luciana
Abstract: BACKGROUND: Single cultivar 'Olivastro di Bucchianico' extra virgin olive oil is obtained from olives cultivated in a narrow area of the Abruzzo region, Italy. This cultivar is mostly present in the municipality of Bucchianico and in some neighbouring municipalities in the province of Chieti. There is very little research in the literature describing the morphological and chemical characteristics of this cultivar. RESULTS: A morphological characterization of the plant and the fruit was carried out. In addition, we characterized the chemical, physical‐chemical and sensory properties of the extra virgin olive oil. The following analyses were conducted: free acidity, peroxide value, ultraviolet spectrophotometric indices, contents in fatty acid ethyl esters, waxes, tocopherols, fatty acids, triglycerides, sterols, alcohols, phenolic substances, volatile compounds and sensory profile. The analysis of the volatile compounds was performed using a headspace‐gas chromatography‐ion mobility spectrometry (HS‐GC‐IMS) instrument connected to a nitrogen generator for carrier/drift gas production. CONCLUSION: The results of the chemical analyses showed good levels of nutraceutical components in the oils, which were found to be organoleptically well balanced with medium values of fruity, bitter and pungent. The HS‐GC‐IMS method based on the analysis of 15 volatile molecules might be a useful tool for a chemometric discrimination of the varietal origin for the oils under investigation. © 2021 Society of Chemical Industry.